Perspective on regulation of caning in the preparation of the criminal law code (KUHP) in the future - Eko Rinawan (Requisitoire Law Enforcement, 2022)
This writing aims to understand the reality of norms regarding the regulation of caning in qanuns or local regulations in the Province of Nanggroe Aceh Darussalam, then to explain how the weaknesses and advantages of regulation of caning as positive law, then to examine the perspective of regulation of caning in the Book of Laws Penal Code (KUHP) in the future as one type of alternative punishment that can be imposed by judges. As for the formal criminal law, it is regulated in the provisions of the Governor of Aceh Regulation Number 10 of 2005 concerning Technical Instructions for Implementation of the Caning Law. This caning punishment is felt to be able to deter the convict because it creates a greater embarrassment effect, resocializes the convict in society and is expected to be able to reduce the crime rate. Caning is a type of punishment that is physically painful. The emergence of many cons regarding its existence because the punishment of caning is considered to tend to degrade human dignity and it is everyone's right to be free from torture. Article 1 paragraph (3) provides a strong legal basis for unwritten laws that live in society regarding the application of customary criminal law. This is solely to fulfill the sense of justice that lives in a certain society. Whereas Article 1 paragraph (4) places caning as a source of material law. So the judge has the authority to multiply the laws that live in society and pass a criminal sentence based on his convictions.